Legalitas dan Motivasi NATO (North Atlantic Treaty Organization) dalam Melakukan Intervensi Kemanusiaan di Libya - Jerry Indrawan (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2013)
The Arab Spring phenomena attack Tunisia, Yemen, and Egypt in early 2011, has finally infected Libya. Massive demonstration toward Colonel Muammar Gaddafi carried out by a group of people in the society that want changes in Libya to be more democratic. In order to maintain his leadership and control over Libya, Gaddafi has no hesitation to use military strength to face the demonstrator. Consequently, many civilian become casualties of such use of force. Based on the situation in Libya, The United Nation (UN) takes action. The UN Security Council issued UN Resolution 1970, and then followed by UN Resolution 1973. This UN Resolution 1973 then used to legitimate NATO in conducting their so called humanitarian intervention to Libya. This course of action is done without UN consent. In other words, NATO sent their multinational forces, lead by the United States, to perform an invasion to a sovereign state. This paper will observe NATO reason and motivation to justify their action in Libya. Do they really want to uphold human rights by saving lives or its only part of their campaign to extend their power, to have a full control over Libya. It is very interesting for us to see how NATO legitimated themselves, and also what motivate them to do such operation in Libya.Keywords: Humanitarian Intervention, NATO Legality and Motivation, the United States Involvement, and Oil.